Studies on standardization of acclimatization of micropropagated bitter gourd (Momordica charantia) plants - SAHA, SWATI; BEHERA, T K (The Indian Journal of Agricultural Sciences, 2015)
Tissue culture has tremendous impact on the crop improvement programme for rapid multiplication in different vegetable crops. However, large scale mortality of plantlets raised through tissue culture occurs during acclimatization phase (Stage IV), i.e. glasshouse and later at field transfer. Micropropagated plants are generally susceptible to rapid dessication when exposed to relative humidity and therefore require proper acclimatization procedure. The ultimate success of micropropagation on a commercial scale depends on the ability to transfer plants out of culture on a large scale, at low cost and with high survival rates. Therefore, acclimatization of micropropagated plants corresponds to a transition period when roots become adapted to a substrate with less available nutrients, and to an autotrophic condition. To ameliorate this problem in bitter gourd (Momordica charantia L.), standardization of acclimatization is very important which is the main objective of this study. The microshoot survival was maximum with glass jar with PP cap in the shoot tip of DBGy 201 with 65.61% while maximum number of leaves/plantlet was highest in the apical meristem of Pusa Vishesh (8.07) and the plant height was also observed to be maximum when glass jar with PP cap was used being highest in the shoot tip of DBGy 201 (15.02 cm). For acclimatization the glass jar with PP caps was found to be the best in respect to establishment in comparison to plastic pots.